Induced Mutation as a Tool for Improving Corm Multiplication in Saffron (Crocus sativus L.) - Naseer1, F.A. Nehvi1; Sajad Majeed Zargar2, M.A. Khan1*, Shaheena Nagoo1, Sabina (Journal of Phytology, 2011)
An attempt was made to create new variants for increasing corm production per planting cycle through the induction of mutations using physical [Gamma rays in Kilo-Roentgen (kr)] and chemical (Ethyl Methane Sulphonate, Colchicine, Ethidium bromide) mutagens at different growth stages of saffron using fortnight treatments (Ist June, 15th June, Ist July, 15th July, Ist August, 15th August, Ist September, 15th September). Initially, 44 plants were selected on the basis of their higher yield performances. Further evaluation of those 44 selected mutagenic plants in M3 generation during the year 2010 identified the treatments D2T6 (15th June treatments of corms with 0.1% EMS) and D8T6 (15th June treatment of corms with Colchicine 0.05%) both produced highest number of daughter corms (15) per mother corm followed by D2T2 (15th June treatment of corms with 0.2kr gamma radiations) producing 12 daughter corms per mother corm, as compared to control (Natural Population) producing only 5 daughter corms per mother corm. Thus, 15th June is proposed as ideal time for treatment of saffron corms in order to induce increased number of daughter corms per mother corm. Further 0.2kr dose gamma radiation is having positive effect on increasing number of daughter corms per mother corm. Standardization of such technique could add to economic stability of farmers, make available considerable quantity of saffron corms for area expansion and by that add to the saffron area and production of our country.